Decreased CFTR/PPARγ and increased transglutaminase 2 in nasal polyps. Issue 6 (December 2022) - Nguyen, Thi Nga; Suzuki, Hideaki; Yoshida, Yasuhiro; Ohkubo, Jun-ichi; Wakasugi, Tetsuro; Kitamura, Takuro
Abstract: Objective: Transglutaminase (TGM)2 and peroxisome proliferator-activated receptor (PPAR)γ are thought to participate in the pathogenesis of nasal polyp formation in cystic fibrosis (CF). We herein investigated expressions of cystic fibrosis transmembrane conductance regulator (CFTR), TGM2, PPARγ and isopeptide bonds, a reaction product of TGM, in non-CF nasal polyps. Methods: Nasal polyps and inferior turbinates were collected from chronic rhinosinusitis patients without CF during transnasal endoscopic sinonasal surgery. Expressions of CFTR, TGM2, isopeptide bonds and PPARγ were examined by fluorescence immunohistochemistry and quantitative RT-PCR. Expression of CFTR was also analyzed by Western blot. Results: Immunohistochemical fluorescence of the nasal polyp was significantly lower for CFTR and PPARγ, and significantly higher for TGM2 and isopeptide bonds than that of the turbinate mucosa. Lower expression of CFTR in the nasal polyp than in the turbinate mucosa was also observed in Western blot. Expression of PPARG mRNA was significantly lower in the nasal polyp than in the turbinate mucosa, whereas expressions of CFTR mRNA or TGM2 mRNA did not differ between the two tissues. Immunohistochemical fluorescence for CFTR showed significant negative correlation with that for TGM2 and isopeptide bonds, and significant positive correlation with that for PPARγ. The fluorescence for TGM2 was positively correlated with that for isopeptide bonds and negatively correlated with that for PPARγ. The fluorescence for isopeptide bonds tended to be negatively correlated with that for PPARγ. Conclusions: These results suggest a possible role of the CFTR-TGM2-PPARγ cascade in the pathogenesis of nasal polyp formation in non-CF patients as in CF patients.